Hope dan Optimisme: Diskursus Perkembangan Ekonomi Syariah Di Indonesia - Muniroh, Alimul (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2018)
Sharia economy has experienced quite rapid development in Indonesia. Its development occurs in the conceptual and practical context. The rise of financial institutions that use sharia principles and various scientific forums carried out studies that are concentrated in the field of sharia economics, even sharia economics sped into a program of one of the leading studies, especially in Islamic-based universities. This study aims to describe the development of Islamic economics in Indonesia in the context of hope and optimism. Hope and optimism studies are psychology-based studies that emphasize positive things in achieving goals. The focus of this study is to explain how the expectations and optimism of Islamic economics in Indonesia. The results of the study show that the belief in the future of the Islamic economy is based on optimism. Strong optimism for the future of the Islamic economy is supported by a responsive view of economic changes in the midst of society.